Ritual functions of clothing in the memorial rites of the Chuvashs - Igor G. Petrov (Publishing house "Sreda", 2024)
Clothes perform many functions functions. One of them is the ritual function, according to which it becomes an important tool or object of various magical practices. In this article, using the example of the сhuvashs of the Volga-Ural region, the functions of the deceased's clothes in the customs and rituals of the memorial cycle are considered. On separate thematic blocks, the role of clothing as a ritual item at large commemorations, at the fortieth day commemoration, as well as at general summer commemorations was investigated. The article is based on published works on the history and ethnography of the chuvashs of the 19th - early 20th centuries, archival sources, as well as field materials of the author collected in different years in the Republic of Bashkortostan and the Republic of Tatarstan. It has been revealed that in the funeral rites, clothes appear and are actively used as a substitute for the deceased, as well as an offering addressed to the deceased on behalf of living relatives. Thanks to these qualities, clothing is one of the important and universal means of communication between the world of the living and the world of the dead. Rites with clothes in memorial rites have been preserved and exist in modern ritual practice. Such stability, on the one hand, is due to the deep archaic and conservative funeral rite as a whole, on the other hand, the comparative stability of this ritual to modern innovations.